ANALISIS PERSEPSI PENGGUNA APLIKASI PAYMENT BERBASIS FINTECH MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Edwin Zusrony; Budi Santoso (UNIVERSITAS STEKOM, 2020)
Abstract The presence of Fintech (Financial Technology) services in digital financial inclusion in Indonesia has become a new market share in line with the growth of electronic commerce (e-commerce) which has increased in the last five years. Fintech is currently in great demand and is used because of the ease of doing banking transactions with the support of user friendly technology. In this study using 40 student respondents with a sampling technique using convenience sampling associated with Fintech-based payment applications using the Technology Acceptance Model (TAM) approach. The purpose of this study is to find out how enthusiastic the young generation or students are in the perception of acceptance of Fintech-based payment application technology. Based on the analysis using quantitative descriptive approach shows that most respondents strongly agree with the existence of this technology indicated by the acquisition of perceived usefulness, perceived ease of use, attitude towards using, behavioral intention to use, and actual system use percentage ranges of 45-72%.